Comparison of secondary metabolites of two mullein species - Grigorov, Maja; Pavlović, Dragana; Tadić, Vanja; Nešić, Ivana; Zlatković , Bojan (Archives of Pharmacy, 2022)
Mullein flower, leaf, and root are used in the traditional medicine of different countries to treat numerous disorders. Various pharmacological properties have been proven in several Verbascum species: anti-inflammatory, antioxidant, antimicrobial, antiviral, antitussive, etc. Previous phytochemical studies revealed the presence of different classes of secondary metabolites, such as iridoids, phenylethanoid glycosides, flavonoids, saponins, etc. The present study aimed to identify and compare the constituents of ethanol extracts of Verbascum phlomoides and V. speciosum flowers and leaves. The plant material was collected in the vicinity of Bosilegrad, and the extracts were prepared by percolation. RP-HPLC coupled with DAD detection was employed for detection and quantification. Identification of all components was performed using standards, and chromatograms were recorded under the same conditions. The results are presented in mg/g of dry extract. All samples had a high content of phenylethanoid glycoside verbascoside (1.46 - 43.49), a significant amount of iridoids aucubin (18.82 - 101.13) and catalpol (26.48 - 59.13), flavonoids, and phenolic acids. Some flavonoids and phenolic acids were present in both species and plant organs, while others were reserved for leaves/flowers or one of the examined species i.e. leaf extract of V. speciosum contained luteolin-7-O-glucoside (8.27); leaf extract of V. phlomoides chrysoeriol (0.22); flower extract of V. phlomoides cinnamic acid (9.87); and flower extract of V. speciosum apigenin (0.84). In conclusion, these extracts are rich in secondary metabolites, and further studies of pharmacological activities and new potential applications are needed.